Analysis of Airport Operational Performance in Selected Airports of Northern Nigeria - Nwaogbe Obioma R.; Ayinla Akorede Ibrahim; Omoke Victor; Ojekunle Joel A.; Wokili-Yakubu Hauwa (Logi, 2021)
This study focuses on the overall airport operational performance of selected airports in Northern Nigeria using the stochastic Frontier Analysis (SFA) model. STATA version 7 software was used for the data analysis. Data collected from the Federal Airport Authority of Nigeria (FAAN) from all the selected airports from 2001 to 2018 included both domestic and international passengers in the given area. The study focused on measuring the operational performance of all selected airports; its results show that none of the airports under review showed 100% level of productivity benchmark. The study recommended that the airports in the given area can improve their technical performance by reducing the unit costs as well as some other inputs to increase efficiency.